Kearifan Lokal Musikal dalam Lagu-lagu Album Bali Kumara - I Putu Lukita Wiweka Nugraha Putra (Journal of Music Science, Technology, and Industry, 2018)
The topic of this article covers local wisdom in the songs of Bali Kumara first album. The purpose of writing this article is to describe the local wisdom in the songs of the Bali Kumara first album. The method used in this study is descriptive-qualitative. I Komang Darmayuda as a composer of Bali Kumara first Album songs is an informant in this research. The data is audio recording of songs in Bali Kumara first album. The Balinese local wisdom in the songs of Bali Kumara first album lies in the use of tone named titi laras pelog and slendro, as well as the use of the Balinese language such as singgih and sor. Pelog and slendro tones are implemented in the main melodies, either by keyboard instruments, gamelan or vocals. In some songs, there are also other scales, such as diatonic and chromatic, which do not diminish the pelog and slendro colors. Seen from the point of view basa singgih (levels in the Balinese language), most of the songs in the album Bali Kumara uses basa singgih, and some basa sor. Balinese pop songs as one of the profane art that grow and develop in Bali should contain elements of the Baliense local wisdom. The local wisdom contained in the songs of Bali Kumara album can be a foothold for the performers of Balinese pop songs especially composers in creating works, so that the identity of the Balinese pop songs is maintained.